Approach to The Patient With Hypertensive Uveitis and Uveitic Glaucoma (Canadian Eye Care Today, 2025)
Elevated intraocular pressure (IOP) and glaucomatous optic neuropathy are common complications in patients with uveitis. Ocular hypertension occurs in approximately 25% of uveitic patients. In addition, retrospective observational studies have found that 31-77% of patients with ocular hypertension had converted to glaucomatous optic neuropathy over a 10 year period. Ocular hypertension occurs in approximately 35% of children with uveitis, with secondary glaucoma occurring in 11-38%. Many of these children will require surgical glaucoma interventions: 11.5% at 1 year after a diagnosis of ocular hypertension, increasing to 50% by 5 years.  In adults with non-infectious uveitis, the rate of surgical glaucoma interventions is between 20-40%.